Fibular Nerve Injury After Small Saphenous Vein Surgery - Yoshida, Ricardo de Alvarenga [UNESP]; Yoshida, Winston Bonetti [UNESP]; Sardenberg, Trajano [UNESP]; Sobreira, Marcone Lima [UNESP]; Rollo, Hamilton Almeida [UNESP]; Moura, Regina [UNESP] (Elsevier B.V., 2012)
Superficial nerve injuries are very common during varicose vein surgery. In contrast, deep nerve injuries are rare and reported especially when surgery involves the small saphenous vein (SSV). The deep motor nerves most commonly injured are the tibial nerve and the peroneal nerve, which are directly or indirectly affected by extrinsic compression, stretching, or healing process involvement. In this report, two cases of common fibular nerve injury after SSV stripping are described, including treatment used and patient outcomes. Nerve damage mechanisms, anatomy, and prevention strategies are also discussed. In conclusion, fibular nerve damage may occur during SSV stripping. Preventive measures include careful preoperative ultrasonographic investigation of the anatomy of the vein, determining location of the saphenopopliteal joint, and careful dissection far from fibular nerve and restricted to the popliteal fossa.